Eficácia da metilxantina no controle da eimeriose em frangos de corte - Shibuya, Fabio Yuji (2023)
Coccidiosis is a common disease in poultry industry and the etiology is Eimeria sp. The disease is known for its enteric lesions, reduction of the intestinal epithelium reducing the poultry growthing and increasing mortality. The poultry industry is demanding for alternative and natural products in order to treat and/or control avian diseases. Methylxanthine is an alcaloid with stimulant properties and extracted from coffee, tea, chocolate, cocoa tea, guarana or citrus sp. There are several benefits of its use such as the immunomodulatory potential in innate and adaptative immunity like stimulating the production of some cytokines in response to coccidiosis infection. The objective of this study was to evaluate the efficacy of Methylxanthine in the Eimeria acervuline and Eimeria tenella control. Therefore, we compared 60 chicks separated in 3 treatments and maintained for 28 days. Group T (negative control); Group T2 (infected with Eimeria acervuline and Eimeria tenella); and Group T3 (infected with Eimeria acervuline and Eimeria tenella and treated with Methylxanthine dilutes in water (30 ml/L). At 28 days of observation, performance data was obtained and the chicken were euthanized. At the necropsy, intestines and cecum samples were submitted to histopathological analysis. The Mehylxanthine treatment reduced the performance losses and intestinal lesions from Eimeria acervuline and Eimeria tenella as observed in the treated group (T3). The treatment with Methylxantine proved efficacy in the infection control of coccidiosis in broiler.